Lactobacillus rhamnosus GG probiotic enteric regimen does not appreciably alter the gut microbiome or provide protection against GVHD after allogeneic hematopoietic stem cell transplantation. Issue 5 (31st March 2017) - Gorshein, Elan; Wei, Catherine; Ambrosy, Susan; Budney, Shanna; Vivas, Juliana; Shenkerman, Angelika; Manago, Jacqueline; McGrath, Mary Kate; Tyno, Anne; Lin, Yong; Patel, Vimal; Gharibo, Mecide; et al.
Abstract: Graft‐versus‐host disease (GVHD) is a major adverse effect associated with allogeneic stem cell transplant. Previous studies in mice indicated that administration of the probiotic Lactobacillus rhamnosus GG can reduce the incidence of GVHD after hematopoietic stem cell transplant. Here we report results from the first randomized probiotic enteric regimen trial in which allogenic hematopoietic stem cell patients were supplemented with Lactobacillus rhamnosus GG . Gut microbiome analysis confirmed a previously reported gut microbiome association with GVHD. However, the clinical trial was terminated when interim analysis did not detect an appreciable probiotic‐related change in the gut microbiome or incidence of GVHD. Additional studies are necessary to determine whether probiotics can alter the incidence of GVHD after allogeneic stem cell transplant.